Determinants of Motor Vehicle Taxpayer Compliance in Kuningan District - Mahadianto, Moh Yudi; Utami, Syita Dwi; Komara, Acep; Septiani, Tika (EAJ (Economic and Accounting Journal), 2023)
This study aims to determine the effect of taxpayer knowledge, income level, and service quality on motor vehicle taxpayer compliance registered at the SAMSAT Office of Kuningan Regency. This study used primary data, namely a questionnaire distributed to 100 motor vehicle taxpayers. The sampling technique used is convenience sampling. The data analysis methods used in this study are descriptive analysis tests, data quality tests, multiple linear regression analysis, and classical assumption tests. This study's results significantly influence Taxpayer Knowledge of Motor Vehicle Taxpayer Compliance. Meanwhile, the Income and Quality of Service level does not affect the Compliance of Motor Vehicle Taxpayers.